Igualdade de Gênero no Mercado de Trabalho: Identificação de fatores promotores e inibidores e mapeamento de práticas organizacionais a partir da análise de organizações na região de Uberlândia/MG - Santos, Flávia Ivana de Melo (2024)
Contextualization: Gender inequality in the labor market is a persistent challenge, evident in several aspects of daily life, such as salary disparity, the lower presence of women in leadership or management positions, and the low female representation in certain areas of knowledge, frequently discussed topics. Objective: This work aims to identify the factors that promote and inhibit gender equality in the labor market, in addition to mapping organizational practices aimed at this promotion. Method: The analysis method used is based on a systematic review of the literature and a bibliometric analysis, with the aim of identifying possible factors that influence inequalities between men and women in the labor market. After this mapping, primary data was collected, through interviews, and secondary data, to inspect factors and business practices that could promote or inhibit gender equality. The interviewees were selected based on their performance and experience in areas such as People Management, Diversity and Culture, specifically in Uberlândia and the region. The research was carried out in Uberlândia and the region, with the interviewees' statements addressing their relationships with work, society and family. The choice of this location was due to two main factors: Uberlândia is the second largest city in Minas Gerais, with a direct impact on the growth of the city and the companies around it, in addition to the accessibility of the population under study to carry out the research. Results: The results of the analyzes reveal the recurrence of specific factors that contribute to inequality, as well as the emergence of new factors, inspired by female leaders, practices combating inequality and mentoring. Compliance of the research with the PPGAdm concentration area (Regionality and Management) and with the line of research: The study is relevant, as it seeks to analyze and identify the factors that promote, as well as those that impede, equality, thus providing important information for the management area, this information was analyzed in articles, works already published on the topic, with subsequent analysis and prioritization with professionals from Uberlândia/MG. Finally, practices of the organizations where the interviewees work in Uberlândia were also analyzed, aiming to identify practices and actions in relation to the identified factors, allowing the presentation of a compilation with forms of application for organizations in the region to positively impact the field of study along with regionality and organizations in the field of management. Impact and innovative character in intellectual production: The innovative character in the production of work lies in the identification of the factors mentioned, as well as organizational practices, approached through research into texts and works already published on the subject and obtaining primary data from women. Economic, social and regional impact: By presenting factors that promote and inhibit women's participation, as well as possible ways of addressing these aspects in organizations, the work can contribute to economic and social development, nationally and regionally, through changes that can be implemented. Regional implications: In the regional aspect, specifically, the development of the study was carried out with organizations from Uberlândia, focusing on regionally perceived aspects and also presenting references from the same territory, such as the possible products generated (reports, interviews, communications, among others). Sustainable Development Goals met in the research: The research meets Sustainable Development Goals 5, 8 and 10, reinforcing the importance of sustainable development combined with gender equality, reducing inequalities and promoting decent, fair and equal work, contributing to economic and social development.